Teman Sebaya dan Paparan Media Sosial dengan Perilaku Konsumsi Jajanan Sehat Pada Anak Usia Sekolah - Pitaloka, Rika Apriani; Milliyantri Elvandari; Linda Riski Sefrina (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2026)
School children's snacks (PJAS) refer to foods and beverages consumed by children during school hours and may be influenced by social factors around them. Peer groups and social media are two factors that can shape children's healthy snacking behavior. This study aims to determine the relationship between peer influence and social media exposure with healthy snacking behavior among elementary school students. This study used a quantitative design with a cross-sectional approach. A total of 43 sixth-grade students at SDN Palumbonsari II, Karawang, were selected using purposive sampling. Data were collected through questionnaires and analyzed using univariate and bivariate analysis with the chi-square test. The results showed that most respondents had good peer relationships (74.4%) and were exposed to social media (81.4%). However, the chi-square test results showed no significant relationship between peer influence and healthy snacking behavior (p = 0.434), nor between social media exposure and healthy snacking behavior (p = 0.826). The conclusion of this study is that there is no significant relationship between peer influence and social media exposure with healthy snacking behavior among students at SDN Palumbonsari II.